Determination of the probability of favorable trends in the export-import of tourist services of Ukraine with EU countries: financial background - Totska, Olesia Leontiivna (University of Agronomic Sciences and Veterinary Medicine of Bucharest, 2023)
The purpose of this article is to analyze the dynamics of financial indicators of export-import of travel-related services between Ukraine and the EU, to identify their favorable trends in the short term. Data from the State Statistics Service of Ukraine for 2014–2021 on the annual volumes of foreign trade in services of Ukraine with the countries of the world, dynamics of foreign trade in services by types were used for the analysis. To identify favorable trends in indicators, a probabilistic forecasting method is used, the basis of which is the use of the Poisson distribution law. The obtained results indicate that the largest recipients of Ukrainian tourist services in the analyzed period were the following EU countries: Cyprus, France, Germany, Italy, Poland (more than 1 million US dollars annually). At the same time, tourism services worth more than 10 million US dollars were imported to Ukraine annually from Cyprus, Germany, Greece, Malta (except for the indicator from Greece for 2020). Bulgaria, Cyprus and Finland have the highest probability of a favorable trend (>0.65) for 1 year for the financial indicators of the export of tourist services from Ukraine; Lithuania, Portugal, and Romania – for indicators of import of tourist services to Ukraine. It will be possible to compare the obtained results with the actual data in May-June 2023, when the State Statistics Service of Ukraine will publish statistical information for 2022. However, a war on the territory of Ukraine may prevent the predictions from coming true.
Keywords: export; import; tourist services; Ukraine; EU countries